LEGAL POLITICS OF CORPORATE CRIME IN INDONESIA - Huda, Misbahul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
A corporation is often followed by violations or even unlawful acts, including violations of criminal law. Corporate crime can also be categorized as an organized transnational crime. At this time corporations as legal subjects can be subject to criminal charges. By accommodating the position of corporations as subjects of general criminal law, corporations can be considered as perpetrators of criminal acts like humans as legal subjects. Unlike before, where the position of the corporation as a subject of criminal law is only accommodated by laws outside the Criminal Code which regulates certain offenses. The regulation outside of the Criminal Code makes the regulation of corporations a subject of criminal law and their criminal liability differs from one regulation to another. With the regulation in the R-KUHP, of course, it will also make uniform regulations regarding corporations as a subject of criminal law, so that there is no difference. However, the regulation of corporations as a subject of criminal law, the current R-KUHP concept is still considered to have shortcomings, because it uses the identification doctrine as the basis for criminal liability